Imagining Politics - Palmer, Bryan D. (Labour / Le Travail, 2014)
Argues in this concluding commentary that the Harper Conservatives have captured the political imagination, while those in opposition have not. Discusses the ideological turn to global neoliberalism, including in Canada, since 1975, as advocated by economist Milton Friedman; in this context, the Harper Conservatives are simply a leaner and meaner version of the trend. Takes note of the contested perspectives on the state and community. Points to social movements, such as the student movement in Quebec, that have attempted to push back. Concludes that the New Right must be challenged by a coherent left politics that is beyond the current party system.
Keywords: CANADA -- Politics & government -- 1980-; CAPITALISM -- Political aspects; CONSERVATIVE Party of Canada (2003- ); Canada; FRIEDMAN, Milton, 1912-2006; HARPER, Stephen, 1959-; Historiography; Neoliberalism